An experimental and numerical study on the mechanical properties of carbon nanotube-latex thin films. Issue 9 (August 2016) - Wang, Long; Loh, Kenneth J.; Brely, Lucas; Bosia, Federico; Pugno, Nicola M.
Abstract: Multi-walled carbon nanotube (MWNT)-latex composite thin films of different MWNT concentrations were fabricated by spraying. Post-fabrication thermal annealing was then conducted on sample sets of different MWNT concentrations, and their microstructure, morphology, and mechanical properties were compared to non-annealed sample sets. The incorporation of MWNTs significantly enhanced the mechanical properties of these nanocomposites at least up to 3 wt%. In addition, annealing altered the microstructure and morphology of the latex matrix, which enhanced the interactions between MWNTs and the polymer, significantly increasing the composite ultimate failure strain and tensile strength. Furthermore, the reinforcing effects of MWNTs on the polymer matrix were investigated using numerical simulations. Stress concentrations were found to initiate at MWNT ends, thus giving rise to yielding fronts that tend to coalesce and propagate across the entire film. The enhancement of the mechanical properties of MWNT-latex nanocomposites, also verified numerically, makes them more suitable for field application as multifunctional coatings or sensors.